2013
DOI: 10.1017/s1461145713000163
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of prelimbic medial prefrontal cortex in panic-like elaborated defensive behaviour and innate fear-induced antinociception elicited by GABAA receptor blockade in the dorsomedial and ventromedial hypothalamic nuclei: role of the endocannabinoid CB1 receptor

Abstract: It has been shown that GABAA receptor blockade in the dorsomedial and ventromedial hypothalamic nuclei (DMH and VMH, respectively) induces elaborated defensive behavioural responses accompanied by antinociception, which has been utilized as an experimental model of panic attack. Furthermore, the prelimbic (PL) division of the medial prefrontal cortex (MPFC) has been related to emotional reactions and the processing of nociceptive information. The aim of the present study was to investigate the possible involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 95 publications
1
30
0
Order By: Relevance
“…In this context, increased Crhr2 binding was also detected in the VMH of wistar rats bred to demonstrate hyper-anxiety/depressive-like phenotype (37). Importantly, the current study also highlights the Cg1 and PrL cortex as implicated in the detected behavioral phenomena, in line with the association of these brain targets with depressive and anxiety disorders in human and animal models (33, 34, 3840). Given the evidence for PrL-modulation of VMH/DMH-induced panic-like behavior in mice, probably via the pathways connecting these structures (33, 34), it is possible that RIP140 might have a systemic, rather than discrete modulatory role within this pathway.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this context, increased Crhr2 binding was also detected in the VMH of wistar rats bred to demonstrate hyper-anxiety/depressive-like phenotype (37). Importantly, the current study also highlights the Cg1 and PrL cortex as implicated in the detected behavioral phenomena, in line with the association of these brain targets with depressive and anxiety disorders in human and animal models (33, 34, 3840). Given the evidence for PrL-modulation of VMH/DMH-induced panic-like behavior in mice, probably via the pathways connecting these structures (33, 34), it is possible that RIP140 might have a systemic, rather than discrete modulatory role within this pathway.…”
Section: Discussionsupporting
confidence: 82%
“…Both nuclei are depicted as part of a neurobiological substrate controlling rodents’ avoidance and defensive behaviors, related to fear, anxiety and panic-like responses (31, 32). Specifically, the manipulation of GABAA receptor in both nuclei was shown to modulate rodents’ defensive behaviour, utilized as an experimental model of panic attack (33, 34). Also, CNS-specific, knockout of the nuclear receptor steroidogenic factor 1 (SF-1), mostly affecting the VMH, was found to result in increased anxiety-like behavior in rodents (35, 36), possibly through altered distribution of stress and anxiety-like behavior related genes, including BDNF and the type-2 receptor for CRH (Crhr2) [for review, see (35)].…”
Section: Discussionmentioning
confidence: 99%
“…Some other studies support the involvement of DMH in the organization of instinctive fear-induced responses [51,52,53,54]. In addition, Cullinan et al [55] showed that stressful stimuli such as swimming and restraining activate DMH.…”
Section: Discussionmentioning
confidence: 86%
“…Fear-induced antinociception has been described as the result of electrical and chemical stimulation of the periaqueductal grey matter, the deep layers of the superior colliculus (Coimbra et al, 1992;Coimbra and Brandão, 1997;Coimbra et al, 2006;da Silva et al, 2013b) and the medial hypothalamus (Freitas et al, 2009;Biagioni et al, 2012;de Freitas et al, 2013de Freitas et al, , 2014. However, similar antinociceptive responses can also be elicited after the tonic immobility defensive behaviour, experimentally induced by postural inversion with slightly restriction of movements (Ferreira and Menescal-de-Oliveira, 2012), in which endogenous opioid peptides, GABAergic and serotonergic mechanisms are critically involved.…”
Section: Discussionmentioning
confidence: 99%